Angiotensin II Type 1 Receptors and Systemic Hemodynamic and Renal Responses to Stress and Altered Blood Volume in Conscious Rabbits - Xu, Tony B.; Eppel, Gabriela A.; Head, Geoffrey A.; Evans, Roger G. (Frontiers in Physiology, 2011)
We examined how systemic blockade of type 1 angiotensin (AT1-) receptors affects reflex control of the circulation and the kidney. In conscious rabbits, the effects of candesartan on responses of systemic and renal hemodynamics and renal excretory function to acute hypoxia, mild hemorrhage and plasma volume expansion were tested. Candesartan reduced resting mean arterial pressure (MAP, -8 ± 2%) without significantly altering cardiac output (CO), increased renal blood flow (RBF, +38 ± 9%) and reduced renal vascular resistance (RVR, -32 ± 6%). Glomerular filtration rate (GFR) was not significantly altered but sodium excretion (UNa+V) increased four-fold. After vehicle treatment, hypoxia (10% inspired O2 for 30 min) did not significantly alter MAP or CO, but reduced HR (-17 ± 6%), increased RVR (+33 ± 16%) and reduced GFR (-46 ± 16%) and UNa+V (-41 ± 17%). Candesartan did not significantly alter these responses. After vehicle treatment, plasma volume expansion increased CO (+35 ± 7%), reduced total peripheral resistance (TPR, -26 ± 5%), increased RBF (+62 ± 23%) and reduced RVR (-32 ± 9%), but did not significantly alter MAP or HR. It also increased UNa+V (803 ± 184%) yet reduced GFR (-47 ± 9%). Candesartan did not significantly alter these responses. After vehicle treatment, mild hemorrhage did not significantly alter MAP but increased HR (+16 ± 3%), reduced CO (-16 ± 4%) and RBF (-18 ± 6%), increased TPR (+18 ± 4%) and tended to increase RVR (+18 ± 9%, P = 0.1), but had little effect on GFR or UNa+V. But after candesartan treatment MAP fell during hemorrhage (-19 ± 1%), while neither TPR nor RVR increased, and GFR (-64 ± 18%) and UNa+V (-83 ± 10%) fell. AT1-receptor activation supports MAP and GFR during hypovolemia. But AT1-receptors appear to play little role in the renal vasoconstriction, hypofiltration and antinatriuresis accompanying hypoxia, or the systemic and renal vasodilatation and natriuresis accompanying plasma volume expansion.